Heat-induced temperature sensitivity of outgrowing Bacillus cereus spores. - Johnson, K M (1984)
Inactivation of Bacillus cereus spores during cooling (10 degrees C/h) from 90 degrees C occurred in two phases. One phase occurred during cooling from 90 to 80 degrees C; the second occurred during cooling from 46 to 38 degrees C. In contrast, no inactivation occurred when spores were cooled from a maximum temperature of 80 degrees C. Inactivation of spores at a constant temperature of 45 degrees C was induced by initial heat treatments from 80 to 90 degrees C. The higher temperatures accelerated the rate of inactivation. Germination of spores was required for 45 degrees C inactivation to occur; however, faster germination was not the cause of accelerated inactivation of spores receiving higher initial heat treatments. Repair of possible injury was not observed in Trypticase soy broth (BBL Microbiology Systems), peptone, beef extract, starch, or L-alanine at 30 or 35 degrees C. Microscopic evaluation of spores outgrowing at 45 degrees C revealed that when inactivation occurred, outgrowth halted at the swelling stage. Inhibition of protein synthesis by chloramphenicol at the optimum temperature also stopped outgrowth at swelling; thus protein synthesis may play a role in the 45 degree C inactivation mechanism.